Preparation method and application of CuI-MCOF sensitive material based on dia topological structure
By preparing CuI-MCOF sensitive materials based on dia topology, the problems of low sensitivity and poor selectivity of hydrofluoric acid detectors in the prior art are solved, and the high-response and low cross-sensitivity hydrogen fluoride detection effect is achieved, which is in line with the development concept of green and environmental protection.
Patent Information
- Application Number
- CN202411873928.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The gas sensors used in the prior art for detecting hydrofluoric acid have problems such as low sensitivity, poor selectivity and high cross sensitivity, and lack of highly responsive sensitive materials.
Cu4I4(py-CHO)4 clusters and para-phenylenediamine were prepared by Schiff base reaction using CuI-MCOF-sensitive material based on dia topology to form CuI-MCOF material with excellent selectivity and cross sensitivity.
It realizes high sensitivity detection of hydrogen fluoride, has excellent HF selectivity and anti-interference ability, and can detect ppb-level HF gas at room temperature, which is in line with the development concept of green and environmental protection.
Smart Images

Figure CN119708399A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas detection, and in particular to a preparation method and application of a CuI-MCOF sensitive material based on a dia topological structure. Background Art
[0002] As an essential etchant and key chemical raw material, hydrofluoric acid (HF) is widely used in semiconductor technology, lens surface processing, chemical raw materials, biopharmaceuticals and other industrial production. However, hydrofluoric acid is volatile and can quickly escape from the solvent at 19°C, causing strong irritation and corrosion to human skin, eyes, respiratory tract and digestive tract mucosa, and may even cause permanent damage. The permissible exposure limit of hydrofluoric acid is only 3ppm, and the short-term exposure limit is 6ppm.
[0003] The analytical methods currently used to measure hydrofluoric acid in industrial environments mainly include: spectroscopy, potentiometry and electrochemical methods, but these methods often require expensive and bulky instruments and equipment, and the hydrofluoric acid gas sensors that have been reported so far generally have problems such as slow response speed, low sensitivity and insufficient minimum detection line.
[0004] Chemi-resistance gas sensors are ideal for detecting hydrogen fluoride content due to their simple structure, wide range of material sources, easy integration, miniaturization, and convenient online monitoring. However, there are few reports on semiconductor chemiresistor gas sensors for hydrogen fluoride detection, and no highly responsive sensitive materials with excellent hydrofluoric acid selectivity and cross sensitivity have been found.
[0005] Therefore, there is an urgent need for a sensitive material with high sensitivity and selectivity to hydrofluoric acid that can be used in a chemical resistance gas sensor. Summary of the invention
[0006] The purpose of the present invention is to provide a preparation method and application of a CuI-MCOF sensitive material based on a dia topological structure, so as to solve the problem of lack of corresponding sensitive materials for detecting hydrogen fluoride using a chemical resistance type gas sensor. The present invention uses a tetraaldehyde-modified Cu4I4(py-CHO)4 cluster and p-phenylenediamine as precursors, and successfully prepares a three-dimensional five-fold cluster-based COF material with a dia topological structure through a Schiff base reaction, named CuI-MCOF, which solves the problems of selectivity, cross sensitivity and high response of HF sensors.
[0007] To achieve the above object, the first aspect of the present invention provides a method for preparing a CuI-MCOF sensitive material based on a dia topological structure, comprising the following steps:
[0008] (1) adding copper iodide powder and pyridine to an organic solvent, heating to reflux, then cooling to room temperature, washing and drying to obtain Cu4I4(py)4 powder;
[0009] (2) dispersing Cu4I4(py)4 powder in an organic solvent, then adding tri(m-tolyl)phosphine, heating to reflux, then cooling to room temperature, washing and drying to obtain Cu4I4(P-(m-Tol)3)4 powder;
[0010] (3) dispersing Cu4I4(P-(m-Tol)3)4 powder in water, then adding 4-formylpyridine, stirring at room temperature, and then centrifuging, washing and drying to obtain Cu4I4(py-CHO)4 powder;
[0011] (4) Cu4I4(py-CHO)4 powder and p-phenylenediamine are mixed in a mixed solution and emulsified to obtain a uniform dispersion. After multiple vacuum freeze-thaw degassing cycles, the dispersion is vacuum sealed, heated, centrifuged, washed, and dried to obtain a CuI-MCOF sensitive material.
[0012] Preferably, in step (1), the molar ratio of copper iodide to pyridine is 1:(3-5).
[0013] Preferably, in step (1), the organic solvent is ethanol, copper iodide is dispersed in ethanol to form a first dispersion, and then pyridine is added dropwise to the first dispersion at 35 to 45° C., refluxed for 0.5 to 1.5 h, and then cooled to room temperature.
[0014] Preferably, in step (2), the molar ratio of Cu4I4(py)4 powder to tri(m-tolyl)phosphine is 1:(0.4-0.6).
[0015] Preferably, in step (2), the organic solvent is ethanol, the Cu4I4(py)4 powder is dispersed in ethanol to form a second dispersion, and then tri(m-tolyl)phosphine is added to the second dispersion at 55-65°C, refluxed for 10-15 hours, and then cooled to room temperature.
[0016] Preferably, in step (3), the mass ratio of Cu4I4(P-(m-Tol)3)4 powder to 4-formylpyridine is 1:(1-1.5).
[0017] Preferably, in step (4), the mass ratio of Cu4I4(py-CHO)4 powder to p-phenylenediamine is 1:(1.1-1.5).
[0018] Preferably, in step (4), the mixed solution comprises 1,4-dioxane, mesitylene and acetic acid solution in a volume ratio of 8:2:1, and the concentration of the acetic acid solution is 5.5 to 6.5 mol / L;
[0019] Cu4I4(py-CHO)4 powder and p-phenylenediamine were added to a Schlenk tube, and then the mixed solution was added and emulsified for 15 to 30 minutes to form a uniform dispersion. The dispersion was flash frozen under liquid nitrogen vacuum conditions, and subjected to three vacuum freeze-thaw degassing cycles. The dispersion was vacuum sealed and heated at 60 to 80°C for 2 to 8 days. The dispersion was then centrifuged, washed and dried to obtain the CuI-MCOF sensitive material.
[0020] The second aspect of the present invention provides an application of a CuI-MCOF sensitive material, and the application of the CuI-MCOF sensitive material in the detection of hydrogen fluoride.
[0021] Preferably, the CuI-MCOF sensitive material is dispersed in ethanol to obtain a third dispersion liquid, and the third dispersion liquid is dropwise applied to the interdigital electrodes with a pipette and then dried to obtain a chemical resistance type gas sensor for hydrogen fluoride detection.
[0022] Therefore, the present invention adopts the above-mentioned structure, a preparation method and application of a CuI-MCOF sensitive material based on a dia topological structure, which has the following beneficial effects:
[0023] (1) The present invention introduces copper iodine clusters with the ability to adjust electronic structure into the sensitive material, thereby enhancing the dipole-dipole interaction between the framework and HF, promoting charge transfer, and improving the conversion and amplification capabilities of the sensing signal.
[0024] (2) The present invention constructs the first chemical resistance type HF gas sensor using CuI-MCOF sensitive material. The CuI-MCOF sensitive material is similar to the olfactory nerve in the human nasal cavity. It achieves specificity for HF gas molecules through a selective amplification process, exhibits ppb-level ultra-sensitive HF gas detection capability at room temperature, and exhibits excellent cross-response anti-interference ability in 13 mixed gases including HF.
[0025] (3) The CuI-MCOF prepared in the present invention is used as a sensitive material for HF gas sensor, and has a response value of 7188% at 100 ppm, showing excellent HF selectivity, cross sensitivity and high response ability, which is in line with the development concept of green environmental protection and comprehensively realizes the unity of economic benefits, social benefits and environmental benefits.
[0026] (4) The excellent HF sensing performance of the CuI-MCOF sensitive material of the present invention not only provides a new idea for the development of a new generation of HF sensors, but also provides an important reference for the study of the structure-performance relationship of three-dimensional cluster-based COFs.
[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the preparation process of CuI-MCOF sensitive materials;
[0029] Figure 2 Infrared spectra of CuI-MCOF, PDA and Cu4I4(py-CHO)4;
[0030] Figure 3 XRD pattern of the 5-fold interpenetrating topology model of CuI-MCOF;
[0031] Figure 4 PXRD spectra of five interpenetrating topological models of CuI-MCOF;
[0032] Figure 5 PXRD spectra of CuI-MCOF and PXRD spectra of 4-6 layer interpenetrating topology model;
[0033] Figure 6 The response of CuI-MCOF sensitive material to various 100ppm gases;
[0034] Figure 7 The response of CuI-MCOF sensitive material to 4ppm HF and other different 100ppm acid gases;
[0035] Figure 8 The response and recovery curves of CuI-MCOF sensitive material to different concentrations of HF at room temperature (RT);
[0036] Fig. 9 The response-concentration logarithmic linear fitting diagram of CuI-MCOF sensitive material;
[0037] Fig.10 Normalized response and recovery time curve of CuI-MCOF sensitive material to 2ppm HF;
[0038] Fig.11 The sensing response of CuI-MCOF sensitive material to 4ppm HF and 100ppm of 12 interfering gases;
[0039] Fig.12 The stability test of CuI-MCOF sensitive material to 4ppm HF within 90 days;
[0040] Fig.13 The response time, recovery time, temperature and LOD value of CuI-MCOF sensitive material are compared with the existing technology;
[0041] Fig.14 This is the appearance of the sensor box;
[0042] Fig.15 is a circuit diagram of a wireless HF sensor system;
[0043] Fig.16 A circuit board for a wireless HF sensor system;
[0044] Fig.17 It is the real-time HF detection chart in the air;
[0045] Fig.18 It is a real-time HF detection diagram in hydrogen fluoride gas;
[0046] Fig.19 This is the real-time HF detection diagram after removing the hydrogen fluoride gas. DETAILED DESCRIPTION
[0047] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0048] Example 1
[0049] like Figure 1 As shown, a method for preparing a CuI-MCOF sensitive material based on a dia topological structure comprises the following steps:
[0050] (1) Synthesis of Cu4I4(py)4 powder
[0051] 0.19 g, 1 mmol CuI powder was dispersed in 20 ml ethanol to obtain a first dispersion. 0.3 g pyridine was added dropwise to the first dispersion at 40°C with stirring. The mixture was refluxed for 1 h. After cooling to room temperature, the mixture was washed three times by centrifugation with ethanol. The white precipitate was vacuum dried at 60°C for 12 h to obtain Cu4I4(py)4 powder.
[0052] (2) Synthesis of Cu4I4(P-(m-Tol)3)4 powder
[0053] Disperse 0.11 g, 0.1 mmol Cu4I4(py)4 powder in 20 ml ethanol to obtain a second dispersion. Add 0.15 g tri(m-tolyl)phosphine to the second dispersion at 60°C with stirring. Reflux for 24 hours. After cooling to room temperature, wash three times with ethanol and toluene by centrifugation. Dry the white precipitate in vacuum at 60°C for 12 hours to obtain Cu4I4(P-(m-Tol)3)4 powder.
[0054] (3) Synthesis of Cu4I4(py-CHO)4 powder
[0055] Take 0.04 g of Cu4I4(P-(m-Tol)3)4 nanoparticles and add them to 40 ml of water to form an aqueous dispersion. Then add 0.25 mmol of 4-formylpyridine to the aqueous dispersion and stir at room temperature for 24 hours. Collect the ligand-exchanged nanoparticles by centrifugation, wash them with water three times, and vacuum dry them at 60°C for 12 hours to obtain an orange-red powder, which is Cu4I4(py-CHO)4 powder.
[0056] (4) Synthesis of CuI-MCOF
[0057] 0.1 g of Cu4I4(py-CHO)4 powder and 0.12 g of p-phenylenediamine (PDA) were added to a 65 mm long Schlenk tube, and then 2 ml of a mixed solution was added. The mixed solution included 1,4-dioxane, mesitylene and 6 M acetic acid in a volume ratio of 8:2:1, and then emulsified for 20 minutes to form a uniform dispersion. The dispersion was flash-frozen under vacuum conditions of liquid nitrogen (77 K), and subjected to three vacuum freeze-thaw degassing cycles. The tube was vacuum-sealed and then heated at 70 ° C for 4 days. The solid matter was collected by centrifugation, washed with DMF, acetone and cyclohexane for more than three times, and dried naturally to obtain the product CuI-MCOF sensitive material.
[0058] Test example
[0059] (1) The sensitive material prepared in the example was characterized by infrared spectroscopy and XRD.
[0060] from Figure 2 It can be seen that the CuI-MCOF sensitive material has a higher relative sensitivity to the reactive monomers (PDA and Cu4I4(py-CHO)4) at 3000-3400 cm -1 The -NH2 vibration peak in the range and at 1712cm -1 The -C=O vibration peak at 1603cm -1 A new -C=N vibration peak appeared at , indicating that an imine bond was generated in the CuI-MCOF sensitive material, confirming that the CuI-MCOF sensitive material was successfully prepared.
[0061] The model of the CuI-MCOF sensitive material was simulated, optimized and refined by powder X-ray diffraction (XRD) combined with theoretical calculation structure simulation (Materials Studio and first-principles simulation package (vasp)), and the crystal structure of the material was further characterized.
[0062] from Figure 3It can be seen that the position and intensity of the diffraction peaks in the experimental PXRD pattern are consistent with the calculation results based on the five-fold independent unit interpenetrating (dia) topological structure model, where the peaks at 6.85° and 9.8° represent the (220) and (211) crystal plane structures, respectively. The unit cell parameters (I41 / AMD space group, α=β=γ=90°) matches well with the model structure (Rwp(w / obck)=7.01%, Rp=8.33%).
[0063] Since independent units may be geometrically interconnected, the 1-fold to 8-fold interpenetration model of CuI-MCOF was also analyzed by theoretical structural simulation. Figure 4 and Figure 5 It can be seen that according to the matching degree between the experimental PXRD pattern and the simulation pattern, it is found that the CuI-MCOF sensitive material prepared by the present invention is indeed a five-fold interpenetrating structure, which further proves that the crystal structure of the CuI-MCOF sensitive material is a five-fold interpenetrating model, excluding other possible interpenetrating models.
[0064] (2) Testing the hydrogen fluoride detection performance of sensitive materials
[0065] The testing process is as follows:
[0066] 10 mg of CuI-MCOF sensitive material was dispersed in 1 ml of anhydrous ethanol solution, and ultrasonicated for 30 minutes to obtain a CuI-MCOF ethanol solution. 20 uL of the CuI-MCOF ethanol solution was drop-coated on the interdigital electrode with a pipette, and the obtained electrode was vacuum dried at 60° C. for 6 hours to obtain a sample. The sample was tested for sensing performance, and a static test system was used during the test of the gas-sensing performance of the device.
[0067] First, the above sample was placed in a 1L sealed quartz glass bottle as a sensor device (referred to as gas cylinder No. 1, and the internal environment was air). The current value of the device was monitored by CHI660e. After the current signal of the device in gas cylinder No. 1 was stable, it was quickly transferred to a 1L plastic bottle containing a certain concentration of HF (referred to as gas cylinder No. 2, the liquid volume of HF with a certain concentration was calculated according to the liquid gas distribution formula, added to bottle No. 2, heated to make HF completely evaporate into gas, and started the test after cooling to room temperature). After the current of the device in gas cylinder No. 2 also reached a sufficiently high and stable value, the sensor was quickly transferred back to gas cylinder No. 1. In addition, during the gas test, the two bottles were cleaned by continuously vacuuming the gas cylinders for 2 minutes. The sensor bias was 3V, and the current was recorded using the CHI660e electrochemical workstation. Responsiveness (R) is used to evaluate the effect of HF on the response, and the calculation formula is:
[0068] R=ΔI / I0,
[0069] Where I0 is the current in air and ΔI represents the change in current in the circuit after exposure to the analytical gas.
[0070] The present invention attaches the sensitive material sample to the interdigital electrode by drop coating method to study the sensing performance of CuI-MCOF sensitive material. Gas selectivity is an important indicator for evaluating gas sensors, and eight representative gases (NH3, NO2, CO2, toluene, ethanol, acetone, HF) at 100ppm are selected to screen the gas-sensing activity of the device.
[0071] like Figure 6 As shown in Figure 2, the CuI-MCOF sensitive material has a response value of 7188% in a 100ppm HF atmosphere at room temperature, but has almost no response value to other gases. In order to further verify the specific response of the CuI-MCOF sensitive material to HF, gas sensing tests were conducted on other different types of organic acids and inorganic acids. Figure 7 It can be seen that when tested under different acidic atmospheres, the response value of CuI-MCOF sensitive material to HF is significantly higher than that of other acidic atmospheres. Even at 4ppm, its HF response value is still 6 times that of 100ppm HCl and 290 times that of HCOOH.
[0072] from Figure 8 It can be seen that the CuI-MCOF sensitive material exhibits concentration-dependent characteristics and high response\recovery characteristics in a wide concentration range (100ppb-100ppm) of HF atmosphere. In particular, even in a low concentration HF (100ppb) atmosphere, there is still a 5% response value, which is far lower than the detection limit of HF leakage by environmental detection (3ppm), indicating that the CuI-MCOF sensitive material has good sensitivity and potential application prospects in low concentration HF detection.
[0073] from Fig. 9 It can be seen that the response-concentration logarithmic linear fitting diagram of CuI-MCOF sensitive material shows a good linear relationship (R 2 =0.99831), the calculated LOD is 11 ppb, which is the lowest among the reported HF-sensitive materials.
[0074] The CuI-MCOF sensitive material exhibits high response / recovery performance over a wide range of HF concentrations. Fig.10 It can be seen that in 2ppm HF atmosphere, the response\recovery time is 4s and 2s respectively. This fast response\recovery time is very beneficial to improving the real-time response of the sensor.
[0075] Under working conditions, the target gas to be detected coexists with other interfering gases in the air, and the ambient humidity also changes in real time. Therefore, anti-interference ability is an important indicator for evaluating the performance of sensing materials. In order to evaluate the reliable selective sensing of HF gas by CuI-MCOF sensitive materials in an interfering environment, 12 interfering gases (NO2, CO2, etc.) were mixed with HF to form a mixed atmosphere. The concentration of the interfering gas was 25 times that of HF. The gas-sensitive sensing test of CuI-MCOF sensitive materials was carried out at room temperature. Fig.11 It can be seen that after 12 common cross-sensitive gases such as acetic acid were mixed with HF, no obvious change in response was observed, indicating that the CuI-MCOF sensitive material prepared by the present invention has good resistance to interference from other gases after being prepared into a sensor. Fig.11 It can also be seen that after mixing 13 gases including HF, the response values detected in four consecutive cycles were all 290%, indicating that even if multiple gases are mixed with hydrogen fluoride at the same time, there is basically no effect on the response of hydrogen fluoride, and the results do not change significantly, which shows that the CuI-MCOF sensitive material has excellent anti-interference ability.
[0076] from Fig.12 It can be seen that in the long-term cycle stability test (measured every 10 days), the CuI-MCOF sensitive material exhibited excellent long-term cycle stability within 90 days, which may be attributed to the stable covalent bond connection in the CuI-MCOF sensitive material framework.
[0077] Taking into account the test temperature, response time, recovery time and LOD value, Fig.13 It can be seen that, compared with the prior art, the CuI-MCOF sensitive material prepared in the present invention is the best HF gas sensor, far exceeding other types of HF sensors reported.
[0078] Other prior art reported in the literature is as follows:
[0079] [1] Devadhasan, JP; Kim, D.; Lee, DY; Kim, S. Smartphone coupled handheld array reader for real-time toxic gas detection. Analytica Chimica Acta, 2017, 984, 168-176.
[0081] [2]Lu,Y.S.;Vijayakumar,S.;Chaix,A.;Pimentel,B,P.;Bentz,K.C.;Li,S.;Chan,A.;Wahl,C.;Ha,J.S.;Hunka,D.E.;Boss,G.R.;Cohen,S.M.;Sailor,M.J.RemoteDetection of HCN,HF,and Nerve Agent Vapors Based onSelf-Referencing,Dye-Impregnated Porous Silicon Photonic Crystals.ACSSensors,2021,6,418-428.
[0082] [3]Hoke,S.H.Hydrogen fluoride analyzer for gases andaerosols.AnalyticaChimicaActa,2002,460,219-225.
[0083] [4]Meulendyk,B.J.;Wheeler,M.C.;Cunha,M.P.D.Hydrogen FluorideGasDetection Mechanism on Quartz Using SAW Sensors.IEEE Sensors Journal,2011,11,1768-1775.
[0085] [5]Wu,M.;Ma,Z.;Fan,Y.;Wu,Y.;An,Z.;Zhao,H.;Liu,Y.;Xu,J.MaterialsDesign,Sensing Performance and Mechanism of Anhydrous Hydrogen Fluoride GasSensor Based on Amino-Functionalized MIL-101(Cr)for New EnergyVehicles.Coatings 2022,12,260-273.
[0086] [6] S.;Zelinger,Z.; V.; Dorogan, A.; Ferus, M.; Iakovlev, V.; Sirbu A.; Mereuta, A.; Caliman, A.; Suruceanu, G.; Kapon, E.
[0087] [7] Appelhans, LN; Finnegan, PS; Massey, LT; Luk, TS; Rodriguez, MA; Brumbach, MT; McKenzie, B.; Craven, J. Transformation of amorphous TiO2
[0088] to a hydronium oxofluorotitanate and applications as an HFsensor.SensorsandActuatorsB Chemical,2016,228,117-123.
[0089] In order to demonstrate the effectiveness of CuI-MCOF-based HF sensors in practical applications, a portable wireless HF sensor system was designed on a printed circuit board. The detailed circuit board design is shown in Figure 15-16 As shown. Figure 14-16 As shown, the sensor box (8*6*8cm) consists of a power module, a sensor module, a microcontroller stm32c8t6, and a wireless data transmission module (low-power Bluetooth unit). The Bluetooth unit supports wireless connection between the sensor module and the computer, and displays the concentration and safety level of HF. For practical applications, a static test method is used to simulate the real environment of the sensor equipment test, and the voltage threshold for the first alarm light to light up is set to 0.1V, corresponding to an HF concentration of 1ppm, and the voltage threshold for the alarm buzzer to sound is set to 0.1V. The second light is 0.2V, corresponding to an HF concentration of 3ppm, and the third light is 0.3V, corresponding to an HF concentration of 5ppm. A syringe is used to create a certain concentration of HF environment, and the response / recovery time of the sensor is only 1 second and 1.4 seconds. The sensor system is used for real-time HF detection ( Figure 17-19), and transmitted to the computer in real time via wireless Bluetooth protocol, showing the dynamic response and recovery of HF sensing. All these results indicate that the designed sensor can effectively perform the task of environmental monitoring, especially HF selective detection.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a CuI-MCOF sensitive material based on a dia topological structure, characterized in that: The following steps are involved: (1) adding copper iodide powder and pyridine to an organic solvent, heating to reflux, then cooling to room temperature, washing and drying to obtain Cu4I4(py)4 powder; (2) Dispersing Cu4I4(py)4 powder in an organic solvent, then adding tri(m-tolyl)phosphine, heating under reflux, then cooling to room temperature, washing and drying to obtain Cu4I4(P-(m-Tol)3)4 powder; (3) Dispersing Cu4I4(P-(m-Tol)3)4 powder in water, then adding 4-formylpyridine, stirring at room temperature, and then centrifuging, washing and drying to obtain Cu4I4(py-CHO)4 powder; (4) Cu4I4(py-CHO)4 powder and p-phenylenediamine are mixed in a mixed solution and emulsified to obtain a uniform dispersion. After multiple vacuum freeze-thaw degassing cycles, the dispersion is vacuum sealed, heated, centrifuged, washed, and dried to obtain a CuI-MCOF sensitive material.
2. The method for preparing a CuI-MCOF sensitive material based on a dia topological structure according to claim 1, characterized in that: In step (1), the molar ratio of copper iodide to pyridine is 1:(3-5).
3. The method for preparing a CuI-MCOF sensitive material based on a dia topological structure according to claim 1, characterized in that: In step (1), the organic solvent is ethanol, copper iodide is dispersed in ethanol to form a first dispersion, and then pyridine is added dropwise to the first dispersion at 35-45° C., refluxed for 0.5-1.5 h, and then cooled to room temperature.
4. The method for preparing a CuI-MCOF sensitive material based on a dia topological structure according to claim 1, characterized in that: In step (2), the molar ratio of Cu4I4(py)4 powder to tri(m-tolyl)phosphine is 1:(0.4-0.6).
5. The method for preparing a CuI-MCOF sensitive material based on a dia topological structure according to claim 1, characterized in that: In step (2), the organic solvent is ethanol, and the Cu4I4(py)4 powder is dispersed in ethanol to form a second dispersion. Then, tri(m-tolyl)phosphine is added to the second dispersion at 55-65°C, refluxed for 10-15 hours, and then cooled to room temperature.
6. The method for preparing a CuI-MCOF sensitive material based on a dia topological structure according to claim 1, characterized in that: In step (3), the mass ratio of Cu4I4(P-(m-Tol)3)4 powder and 4-formylpyridine is 1:(1~1.5).
7. The method for preparing a CuI-MCOF sensitive material based on a dia topological structure according to claim 1, characterized in that: In step (4), the mass ratio of Cu4I4(py-CHO)4 powder to p-phenylenediamine is 1:(1.1-1.5).
8. The method for preparing a CuI-MCOF sensitive material based on a dia topological structure according to claim 1, characterized in that: In step (4), the mixed solution includes 1,4-dioxane, mesitylene and acetic acid solution in a volume ratio of 8:2:1, and the concentration of the acetic acid solution is 5.5-6.5 mol / L; Cu4I4(py-CHO)4 powder and p-phenylenediamine were added to a Schlenk tube, and then the mixed solution was added and emulsified for 15-30 minutes to form a uniform dispersion. The dispersion was flash frozen under liquid nitrogen vacuum conditions, and subjected to three vacuum freeze-thaw degassing cycles. The dispersion was vacuum sealed and heated at 60-80°C for 2-8 days. The CuI-MCOF sensitive material was then obtained after centrifugation, washing and drying.
9. Application of the CuI-MCOF sensitive material obtained by the preparation method according to any one of claims 1 to 8, characterized in that: Application of CuI-MCOF sensitive material in hydrogen fluoride detection.
10. The use of the CuI-MCOF sensitive material according to claim 9, characterized in that: The CuI-MCOF sensitive material is dispersed in ethanol to obtain a third dispersion liquid, and the third dispersion liquid is dropwise applied on the interdigital electrodes with a pipette and then dried to obtain a chemical resistance type gas sensor for hydrogen fluoride detection.
Citation Information
Patent Citations
Cu(I)-based metal organic framework, and preparation method and applications thereof
CN105017239A
Tailing structure covalent organic framework membrane materialand application thereof
CN113736097A
Covalent organic frameworks
CN114981335A
Adsorbent MCOF-DES, synthesis method thereof and application of adsorbent MCOF-DES in detection of copper in environment and / or plant
CN117443358A
Compositions and Methods for the modification of imine covalent organic frameworks (COFs)
US20190161623A1